2014
DOI: 10.1167/iovs.14-15375
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Structure-Function Relationship in Glaucoma With an Anatomically and Geometrically Accurate Neuroretinal Rim Measurement

Abstract: The structure-function relationship was enhanced with BMO-MRW compared with the other neuroretinal rim measurements, due mainly to its geometrically accurate properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 30 publications
3
49
2
3
Order By: Relevance
“…In the current study, applying a correction for the papillomacular tilt significantly changed cpRNFL thickness measurements, in agreement with a previous report. 31 Interestingly, Danthurebandara et al 32 have recently reported that applying a correction for papillomacular tilt did not result in any measurable improvement in the structure-function relationship, which is contradictory to our results. The reason for these conflicting results is not clear but may be attributed to the different measurement site, since the Relative probability is defined as the possibility this model minimizes the information loss, compared with the model with smallest AICc.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, applying a correction for the papillomacular tilt significantly changed cpRNFL thickness measurements, in agreement with a previous report. 31 Interestingly, Danthurebandara et al 32 have recently reported that applying a correction for papillomacular tilt did not result in any measurable improvement in the structure-function relationship, which is contradictory to our results. The reason for these conflicting results is not clear but may be attributed to the different measurement site, since the Relative probability is defined as the possibility this model minimizes the information loss, compared with the model with smallest AICc.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of Danethurebandara et al on optic discs of all sizes, sensitivity of BMO-MRW and RNFLT is not significantly different (p=0.09) 34. Malik et al 30 showed the same similar performance in glaucoma discrimination for 130 individuals with myopic discs.…”
Section: Discussionmentioning
confidence: 66%
“…However, all these were global correlations. Previous studies 22,23,30 have already established regional correlations between RNFL loss, GCC loss, and VF deficits. This study looked at sectoral vascular changes with corresponding regional VF defects.…”
Section: Discussionmentioning
confidence: 98%